2021
DOI: 10.7150/jca.58094
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of C-Reactive Protein to Lymphocyte Count Ratio as a prognostic factor for Survival in Non-small Cell Lung Cancer Patients undergoing Curative Surgical Resection

Abstract: Purpose: We assessed the clinical feasibility of C-reactive protein to lymphocyte ratio (CLR) as a determinant of survival in patients with non-small cell lung cancer (NSCLC) undergoing curative surgical resection. Methods: A retrospective study was conducted on patients with stage I and II NSCLC undergoing curative resection. Demographic and clinical variables, including CLR, were collected and analyzed. The Cox proportional hazards model was used to calculate hazard ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Authors studied pre-operative CLR values of the subjects with oral squamous cell carcinoma and concluded that CLR was associated with better prognostic performance compared to other inflammatory markers and elevated CLR levels indicated poor overall and disease-free survival in this population 16 18 . Moreover, prognostic value of elevated CLR has been also shown in patients with lung cancer 19 , osteosarcoma 20 , and cholangiocarcinoma 21 . It is a fact that malignant conditions are associated with increased inflammatory burden 22 , as seen in patients with COVID-19 infection.…”
Section: Discussionmentioning
confidence: 95%
“…Authors studied pre-operative CLR values of the subjects with oral squamous cell carcinoma and concluded that CLR was associated with better prognostic performance compared to other inflammatory markers and elevated CLR levels indicated poor overall and disease-free survival in this population 16 18 . Moreover, prognostic value of elevated CLR has been also shown in patients with lung cancer 19 , osteosarcoma 20 , and cholangiocarcinoma 21 . It is a fact that malignant conditions are associated with increased inflammatory burden 22 , as seen in patients with COVID-19 infection.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequently, Mungan et al 13 confirmed the results of Meng et al 12 . In addition, prognostic value of elevated CLR has also been shown in patients with osteosarcoma 14 , cholangiocarcinoma 15 , and lung cancer 16 . It is a fact that malignant conditions are associated with increased inflammatory burden 17 , as seen in patients with CHC.…”
Section: Discussionmentioning
confidence: 98%
“…Hwang et al recently demonstrated that the CLR was a determinant biomarker in overall survival and disease-specific survival in gastric carcinoma patients. 45 The higher CLR maybe represent a poor long-term outcome in colorectal liver metastases patients after hepatic resection. 33 Interestingly, there is no report to research the relationship between CLR and diabetes at present; the present study is the first report.…”
Section: Discussionmentioning
confidence: 99%